The Use of 4K Technology in Teaching Geography Lessons - Orifjonova Iroda Orifjon kizi; Sirojeva Jasmina Rustamovna (Scientific Trends, 2024)
In the realm of education, technological advancements continue to redefine traditional teaching methods, offering innovative approaches to engage and educate students. This article explores the integration of 4K technology in geography lessons, examining its potential to enhance learning experiences, foster spatial understanding, and promote immersive exploration. Through a comprehensive analysis, this study evaluates the effectiveness of 4K technology in geography education, presenting findings that underscore its benefits and implications for teaching and learning.
Keywords: 4K technology, geography education, immersive learning, spatial understanding, educational technology.